Immigrants and exports: Firm-level evidence from Canada - Miguel Cardoso; Ananth Ramanaryanan (The University of Western Ontario, Department of Economics, 2019)
We examine how immigrant employment enhances trade at the firm level using unique administrative matched employer-employee data from Canada. We augment a standard model of firms' export market entry and sales decisions with trade costs that depend on destination-specific immigrant employment at the firm level. We estimate simple structural equations derived from the model that relate destination-specific exporting decisions to immigrant employment. We develop a method to deal with the potential endogeneity of immigrant employment that exploits the optimality conditions associated with the firm's employment decision. We find positive and statistically significant effects of firm level immigrant employment on exporting. These effects vary with product type and immigrant employee characteristics in ways consistent with the idea that immigrant employees alleviate information barriers to trade.
Keywords: 330